2013
DOI: 10.1371/journal.pone.0082101
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-Receptor 1 Deficiency Has No Influence on Immune Cell Repertoire or Function during Experimental Autoimmune Encephalomyelitis

Abstract: The potential role of Nogo-66 Receptor 1 (NgR1) on immune cell phenotypes and their activation during neuroinflammatory diseases such as multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE), is unclear. To further understand the function of this receptor on haematopoietically-derived cells, phenotypic and functional analyses were performed using NgR1-deficient (ngr1-/-) animals. Flow cytometry-based phenotypic analyses performed on blood, spleen, thymus, lymph nodes, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…In the acute phase, we showed that the majority of the NgR protein signal (70–75 %) was detected in inflammatory cells of lesioned areas, while lesser signal was acquired from axonal elements of white matter (~10–15 %). Although B and T cell populations were not examined in this study, it has been previously published that NgR deficiency does not affect the immune cell repertoire [ 16 ] nor the clinical outcome of EAE [ 17 ]. On the other hand, NgR has been strongly connected to cell adhesion [ 31 , 32 ], motility of microglia and its regulation [ 22 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acute phase, we showed that the majority of the NgR protein signal (70–75 %) was detected in inflammatory cells of lesioned areas, while lesser signal was acquired from axonal elements of white matter (~10–15 %). Although B and T cell populations were not examined in this study, it has been previously published that NgR deficiency does not affect the immune cell repertoire [ 16 ] nor the clinical outcome of EAE [ 17 ]. On the other hand, NgR has been strongly connected to cell adhesion [ 31 , 32 ], motility of microglia and its regulation [ 22 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The value of the Nogo-NgR pathway for control of axonal regeneration is verified by the development of Nogo-A and LINGO-1 monoclonal antibodies for clinical trials [ 14 , 15 ]. Despite the fact that NgR is key to the pathway activation, only few studies analyzing knockout mice in experimental autoimmune encephalomyelitis (EAE) [ 16 , 17 ] and few small interference RNA (siRNA) experiments have been carried out in demyelination of optic nerve tracts [ 18 , 19 ], rendering its precise function still enigmatic. In vitro experiments by Takahashi and colleagues [ 20 ] and later further progressed by David and colleagues [ 21 , 22 ] suggest that the presence of NgR in macrophages—apart from neurons or glia—could support the clearance of debris and could confine the injury away from the normal-appearing white matter tissue.…”
Section: Introductionmentioning
confidence: 99%
“…φιθςκα ιε ηα ιέπνζ ηχνα αζαθζμβναθζηά δεδμιέκα, μζ απυρεζξ πμο ηαηαηίεεκηαζ ζπεηζηά ιε ημκ νυθμ ημο Nogo-A ζηδκ ΠΑΔ είκαζ ακηζηνμουιεκεξ. Τπάνπμοκ ιεθέηεξ πμο οπμζηδνίγμοκ υηζ ημ ζοβηεηνζιέκμ ιυνζμ δε ζοιιεηέπεζ ζηδκ παεμθοζζμθμβία ηδξ ΠΑΔ [151][152] ηαζ άθθεξ πμο οπμζηδνίγμοκ ηδκ ζοιιεημπή ημο πςνίξ υιςξ κα πνμζδζμνίγμοκ ημκ νυθμ ημο (αηυια ηαζ υηακ δδιμζζεφμκηαζ ηδκ ίδζα πνμκζηή ζηζβιή ηαζ ζημ ίδζμ πενζμδζηυ) [153][154][155] ή πνμζθένμκηαξ εθθζπείξ πθδνμθμνίεξ, ηονίςξ θυβς έθθεζρδξ ακηζπνμζςπεοηζηχκ απεζημκζζηζηχκ δεδμιέκςκ [156][157] ή ηαζ ζε ιενζηέξ πενζπηχζεζξ παναπθακδηζηά υπςξ π.π ζηδκ πενίπηςζδ απυζονζδξ ειπμνζημφ ακηζζχιαημξ [107].…”
Section: θνπόο δηαηξηβήοunclassified